Isolation and Protein Profile of Chicken, Pork and Processed Products Nugget with Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) Method - Orbayinah, Salmah; Widada, Hari; Anindita, Nosa Septiana; Mohdar, Adhe Filiyahtri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Chicken nuggets are known as a nutritious processed meat food ingredient and are widely available in supermarkets and are very popular with consumers. Nugget is made by mixing it with various other additives, so that it raises a bit of concern about the ingredients used in terms of halal. The purpose of this study was to determine and analyze the protein profile of chicken, pork, nugget references, and nugget commercials. The method used in this study is an experimental laboratory analysis of variables using SDS-PAGE (Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis). The data were obtained from observing the description of protein bands, calculations were carried out using linear regression, and descriptive analysis was carried out. The results of this study showed 4 protein bands in pork that were not found in chicken meat with a molecular weight of 62.95 kDa, 41.86 kDa, 31.28 kDa and 17.46 kDa. Based on the protein fraction, the protein referred to as BM 31.28 kDa is Tropomyosin and BM 17.46 kDa is Troponin C. Nugget reference shows similarities to the protein bands found in pork, whereas nugget commercially did not show specific similarity.